2008
DOI: 10.1093/brain/awn109
|View full text |Cite
|
Sign up to set email alerts
|

Debris clearance by microglia: an essential link between degeneration and regeneration

Abstract: Microglia are cells of myeloid origin that populate the CNS during early development and form the brain's innate immune cell type. They perform homoeostatic activity in the normal CNS, a function associated with high motility of their ramified processes and their constant phagocytic clearance of cell debris. This debris clearance role is amplified in CNS injury, where there is frank loss of tissue and recruitment of microglia to the injured area. Recent evidence suggests that this phagocytic clearance followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
783
2
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 906 publications
(819 citation statements)
references
References 71 publications
20
783
2
3
Order By: Relevance
“…Though very sparse OX-positive, activated, microglia cells were found in SP, SL and SR of the three experimental groups, many IBA1-positive, reactive microglia cells (Beynon and Walker 2012) phagocytosed ectopic pyramidal neurons or neuronal debris in CA3 SR of 2VO-vehicle rats. The high motility of microglia that effectively monitor the status of the local surroundings may explain the decrease of microglia in CA3 SP and the increase in CA3 SL and SR where it endocytoses small cellular debris derived from apoptotic cells (Neumann et al 2009). Therefore, post-ischemic production of cytokines and recruitment of microglia to the damaged tissue (Farkas et al 2002) can facilitate tissue repair by increasing phagocytosis or phagoptosis, promoting the resolution of inflammation and exerting direct cytoprotective effects on surviving cells in the ischemic area.…”
Section: Discussionmentioning
confidence: 99%
“…Though very sparse OX-positive, activated, microglia cells were found in SP, SL and SR of the three experimental groups, many IBA1-positive, reactive microglia cells (Beynon and Walker 2012) phagocytosed ectopic pyramidal neurons or neuronal debris in CA3 SR of 2VO-vehicle rats. The high motility of microglia that effectively monitor the status of the local surroundings may explain the decrease of microglia in CA3 SP and the increase in CA3 SL and SR where it endocytoses small cellular debris derived from apoptotic cells (Neumann et al 2009). Therefore, post-ischemic production of cytokines and recruitment of microglia to the damaged tissue (Farkas et al 2002) can facilitate tissue repair by increasing phagocytosis or phagoptosis, promoting the resolution of inflammation and exerting direct cytoprotective effects on surviving cells in the ischemic area.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal injury often leads to proliferation and migration of activated microglia to assist with cellular debris cleanup [55]. It could be hypothesized that activated microglia are ingesting released Mn 2+ during this period, potentially leading to an increase in signal.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we investigated whether rotenone-induced phagocytic activity was dependent of Fc␥ receptors (Fc␥Rs) because Fc␥Rs on microglia contribute to diverse cellular functions and Fc␥R-mediated phagocytosis is associated with the inflammatory activity of microglia. 34,35 FACS analysis using a rat anti-mouse CD16/ CD32 antibody indicated that Fc␥Rs on BV2 microglial cells were up-regulated after exposure to rotenone ( Figure 3B and data not shown). Moreover, rotenone-triggered phagocytic activity was markedly reduced by blocking Fc␥Rs using Fc Block directed against such receptors ( Figure 3C).…”
Section: Microglia Display Typical Activated Properties Under Rotenonmentioning
confidence: 93%